Job protection legislation and productivity growth in OECD countries - Bassanini, Andrea; Nunziata, Luca; Venn, Danielle (Bonn, 2008)
"This paper examines the impact of employment protection legislation on productivity in the OECD, using annual cross-country aggregate data on the degree of regulations and industry-level data on productivity from 1982 to 2003. We adopt a "difference-in-differences" framework, which exploits likely differences in the productivity effect of dismissal regulations in different industries. Our identifying assumption is that stricter employment protection influences worker or firm behaviour, and thereby productivity, more in industries where the policy is likely to be binding than in other industries. The advantage of this approach is that, in contrast with standard cross-country analysis, we can control for unobserved factors that, on average, are likely to have the same effect on productivity in all industries. Our empirical results suggest that mandatory dismissal regulations have a depressing impact on productivity growth in industries where layoff restrictions are more likely to be binding. We present a large battery of robustness checks, including dealing with endogeneity issues, that suggest that our finding is robust. "